MORPHOLOGICAL CHARACTERISTICS OF THE KIDNEYS ON THE 7TH, 14TH AND 21TH DAYS DURING THE PROLONGED PERIOD OF MODERATE BRAIN INJURY (Academia Science Repository, 2023)
This article presents information about the results of scientific studies that allow to evaluate and study the morphological features of the kidneys of 3-month-old rats after moderately severe brain injuries. Morphological analysis of rat kidneys was performed on days 7,14 and 21 after brain injury.